Pengaruh Kompensasi Dan Kepemimpinan Terhadap Disiplin Kerja - Wide Ivano; Febsri Susanti (Universitas 45 Surabaya, 2023)
This study aims to examine the significance of the influence of compensation and leadership both simultaneously and partially on the work discipline of employees at the Public Works and Spatial Planning Office of the City of Padang. This type of research is descriptive with a quantitative approach where the respondents are employees at the Office of Public Works and Spatial Planning in the City of Padang. Determination of the number of samples using the Total Sampling sample technique. The number of samples taken was 77 people to be respondents. The analysis technique used is path analysis to determine the magnitude of the influence of compensation and leadership both simultaneously and partially on the work discipline of employees at the Public Works and Spatial Planning Office of the City of Padang. The results of the study prove that compensation and leadership affect the work discipline of employees at the Public Works and Spatial Planning Office of the City of Padang.